Expanding the Molecular and Clinical Phenotype of SSR4‐CDG. Issue 11 (27th August 2015) - Ng, Bobby G.; Raymond, Kimiyo; Kircher, Martin; Buckingham, Kati J.; Wood, Tim; Shendure, Jay; Nickerson, Deborah A.; Bamshad, Michael J.; University of Washington Center for Mendelian Genomics; Wong, Jonathan T.S.; Monteiro, Fabiola Paoli; Graham, Brett H.; et al.
<x xml:space="preserve">Abstract</x> Congenital Disorders of Glycosylation (CDG) lead to incomplete protein glycosylation. One disorder, SSR4‐CDG, was previously defined in a single patient. Here we present molecular analysis and clinical phenotypes of eight males with inherited and de novo mutations in X‐linked SSR4. Standard CDG biochemical analysis might easily miss them.